2006
DOI: 10.1051/0004-6361:20054522
|View full text |Cite
|
Sign up to set email alerts
|

Circumstellar material in the Vega inner system revealed by CHARA/FLUOR

Abstract: Context. Only a handful of debris disks have been imaged up to now. Due to the need for high dynamic range and high angular resolution, very little is known about the inner planetary region, where small amounts of warm dust are expected to be found. Aims. We investigate the close neighbourhood of Vega with the help of infrared stellar interferometry and estimate the integrated K-band flux originating from the central 8 AU of the debris disk. Methods. We performed precise visibility measurements at both short (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
236
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(255 citation statements)
references
References 58 publications
19
236
0
Order By: Relevance
“…We only calculated the emission spectrum of the dust and ignored the (viewing-angle-dependent) contribution of scattered light, since thermal emission was found to dominate scattered light at the wavelengths in which hot exozodiacal dust is detected (Absil et al 2006). For the analytical dust distributions, we assumed the dust has a black-body temperature (Eq.…”
Section: Comparison With Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We only calculated the emission spectrum of the dust and ignored the (viewing-angle-dependent) contribution of scattered light, since thermal emission was found to dominate scattered light at the wavelengths in which hot exozodiacal dust is detected (Absil et al 2006). For the analytical dust distributions, we assumed the dust has a black-body temperature (Eq.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…The dust can be studied by observing its infrared and (sub-)millimeter emission, as well as the stellar radiation it scatters, and is usually found at large distances from the star (tens of AUs, Carpenter et al 2009). Recently, interferometric observations have found excess nearinfrared (NIR) emission emanating from the innermost parts of several debris disks, which has been interpreted as thermal emission from hot (>1000 K) dust (Ciardi et al 2001;Absil et al 2006Absil et al , 2008Absil et al , 2009di Folco et al 2007;Akeson et al 2009;Defrère et al 2011Defrère et al , 2012 Table 1 for an overview). This material is known as hot exozodiacal dust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For β UMi, we have used the Johnson K-band magnitude of −1.39 , yielding a magnitude of −1.45 in the Selby system. Zeropoints are calculated using the Kurucz theoretical spectrum of Vega (Cohen et al 1992), taking into account the observed near-IR excess of Vega (Absil et al 2006). For the Selby photometric system we obtain a zeropoint of 4.0517 × 10 −10 W/m 2 /μm.…”
Section: Comparison Between Sed and Theoretical Predictionsmentioning
confidence: 99%
“…Their observations have revealed a wide variety of inferred dust masses, disk extents, and even disk morphologies (e.g., Wyatt 2008, and references therein). For example, dust has been detected from well within one AU (Beichman et al 2005;Absil et al 2006), out to hundreds of AU (e.g., Su et al 2005). While the former cases seem to be rare (Wyatt et al 2007), the latter are more commonly reported, corresponding to significantly higher detection rates at longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%